7u+47=3(u+9)

Simple and best practice solution for 7u+47=3(u+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7u+47=3(u+9) equation:


Simplifying
7u + 47 = 3(u + 9)

Reorder the terms:
47 + 7u = 3(u + 9)

Reorder the terms:
47 + 7u = 3(9 + u)
47 + 7u = (9 * 3 + u * 3)
47 + 7u = (27 + 3u)

Solving
47 + 7u = 27 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
47 + 7u + -3u = 27 + 3u + -3u

Combine like terms: 7u + -3u = 4u
47 + 4u = 27 + 3u + -3u

Combine like terms: 3u + -3u = 0
47 + 4u = 27 + 0
47 + 4u = 27

Add '-47' to each side of the equation.
47 + -47 + 4u = 27 + -47

Combine like terms: 47 + -47 = 0
0 + 4u = 27 + -47
4u = 27 + -47

Combine like terms: 27 + -47 = -20
4u = -20

Divide each side by '4'.
u = -5

Simplifying
u = -5

See similar equations:

| X/3=1.8 | | 9-7=8 | | 3x-2(x-5)=7x-4(2x+1) | | 35x-5=x+17 | | -x/6=6/9 | | 5(w-2)-7w=-30 | | x^2-8x+13=-4 | | 2x^7+18x^6+36x^5=0 | | X+22=35x | | 18+19m+m^2=0 | | 1/0*190340 | | -3/8=x/24 | | r^2-6r-83=-10 | | -3n+12-n=40+8 | | 7/10-7=7 | | X/10=7/10 | | v^2-12v+34=-6 | | 2+6x-2x=-8+2x | | A^4-2a^2-35=0 | | 2x+3=3x+-2 | | 81r^2-49= | | 17=kg-2 | | 9x^2+8= | | -8x-(-5)=12x-(-85) | | -3x-(-8)=-9x-28 | | 2x-6=24+3x | | 8x-12=-8x-140 | | 56r=7 | | -5x-1=2x-(-69) | | 8p+4=2p+24 | | 8x-(-8)=-3x+(-124) | | -7(x+4)-16=11+8 |

Equations solver categories